2001
DOI: 10.1007/pl00001241
|View full text |Cite
|
Sign up to set email alerts
|

Aftershock Activity and Frequency-dependent Low Coda Qc in the Epicentral Region of the 1999 Chamoli Earthquake of Mw 6.4

Abstract: Ð On 28 March, 1999 (19:05:10.09, UT) a signi®cant earthquake of M w 6.4 occurred in the Garhwal Himalaya (30.555°N, 79.424°E). One hundred and ten well-recorded aftershocks show a WNW-ESE trending northeasterly dipping seismic zone extending from a depth of 2 to 20 km. As the main shock hypocenter occurred at the northern end of this seismic zone and aftershocks extended updip, it is inferred that the main-shock rupture nucleated on the detachment plane at a depth of 15 km and then propagated updip along a NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 19 publications
0
23
1
Order By: Relevance
“…When we compared the result for the LT = 20 s and WL = 30 s, our results are similar to MUKHOPADHYAY et al (2006) for their analyzed frequency range (0.5-7.0 Hz); however, as compared to KUMAR et al (2005), it is similar at a frequency of B18 Hz while at higher frequencies ([18 Hz) the coda attenuation is higher in this region. The Chamoli region of Himalaya shows higher coda attenuation as compared to the present study region (MANDAL et al, 2001). It may be due to a much more localized study as compared to the present study [epicentral distance range from 1.5 to 47 km, focal depth mainly concentrated from 10 to 15 km (however, focal depth \20 km), and window length range 30-80 s].…”
Section: Comparison With Other Studiesmentioning
confidence: 39%
See 1 more Smart Citation
“…When we compared the result for the LT = 20 s and WL = 30 s, our results are similar to MUKHOPADHYAY et al (2006) for their analyzed frequency range (0.5-7.0 Hz); however, as compared to KUMAR et al (2005), it is similar at a frequency of B18 Hz while at higher frequencies ([18 Hz) the coda attenuation is higher in this region. The Chamoli region of Himalaya shows higher coda attenuation as compared to the present study region (MANDAL et al, 2001). It may be due to a much more localized study as compared to the present study [epicentral distance range from 1.5 to 47 km, focal depth mainly concentrated from 10 to 15 km (however, focal depth \20 km), and window length range 30-80 s].…”
Section: Comparison With Other Studiesmentioning
confidence: 39%
“…The frequency dependency parameter estimated in this region is higher as compared to other regions indicating more heterogeneous upper lithosphere; however, it is similar to that for the northwestern Himalaya, Garwhal Himalaya, Turkey, Italy, Spain. Variation of frequency parameter is also not significant at smaller LT and shallow events in some other parts of the world (IBANEZ et al, 1990; Washington (Havskov et al, 1989) Western Anotolia (Akinci et al, 1994) Kutch (Gupta et al, 2006) Koyna (Gupta et al, 1998) Garhwal Himalaya (Gupta et al, 1995) Western Himalaya (Kumar et al, 2005) Dead Sea (Van Eck, 1988) Western Himalaya (Mukhopadhyay et al, 2006) Colombia (Ugalde et al, 2002) Southern India (Tripathi & Ugalde, 2004) Chamoli (Mandal et al, 2001) Bhuj (Mandal et al, 2004) Koyna (Mandal & Rastogi, 1998) Maxico (Rodriguez et al, 1983 (Gupta et al, 1995) Western Himalaya (Kumar et al, 2005) Western Himalaya (Mukhopadhyay et al, 2006) Chamoli (Mandal et al , 2001) Western et al, 1994). The coda attenuation parameter estimated in the present study is comparable to the estimates obtained by other workers for the Indian lithosphere (GUPTA et al, 1995(GUPTA et al, , 1998(GUPTA et al, , 2006MANDAL and RASTOGI, 1998;MANDAL et al, 2001MANDAL et al, , 2004TRIPATHI and UGALDE, 2004;KUMAR et al, 2005;MUKHOPADHYAY et al, 2006).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…This is the initial study reporting the simultaneous estimation of frequencydependent relationships for Q a and Q b in this region. GUPTA et al (1995) andMANDAL et al (2001) have earlier obtained the coda-Q estimates of the region using single backscattering model (AKI and CHOUET, 1975). The estimates of Q b based on strong motion data of the 1991 Uttarkashi and 1999 Chamoli earthquakes in the region are available (SINGH et al, 2004;DINESH et al, 2005;SRIRAM et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The ratio Q b /Q a is greater than one in the region which along with the frequency dependence of quality factors indicates that scattering is an important factor contributing to the attenuation of body waves in the region. A comparison of attenuation relation for S wave estimated here (Q b = 87f 0.71 ) with that of coda waves (Q c = 30f 1.21 ) obtained by MANDAL et al (2001) for the same region shows that Q c > Q b for higher frequencies (>8 Hz) in the region. This indicates a possible high frequency coda enrichment which suggests that the scattering attenuation significantly influences the attenuation of S waves at frequencies >8 Hz.…”
mentioning
confidence: 99%
“…A total of 204 aftershocks of magnitude varying from 1.4 to 4.8 were recorded by NGRI during 4 April 1999 through 20 May 1999. The estimated hypocentral parameters for these well-located aftershocks delineate three distinct seismic trends corresponding to: 1) a detachment surface dipping at 15° to NNE at depths of 10 -16 km; 2) Munsiari (MCT 2) thrust dipping at 45˚ to NE at depths 2 -16 km; and 3) NE trending transverse fault dipping at 45˚ to SE extending from a depth of 4 to 10 km [30,31]. They also revealed that the mainshock occurred near a junction between the detachment surface and MCT 2 at a depth of 15 km.…”
Section: Seismotectonics and Depth Sections Across Mctmentioning
confidence: 99%